On generating ultrasounds by laser in polymers - RADZISZEWSKI, L. (Archives of Acoustics, 1994)
The paper reports an experimental investigation of the possibility of generating ultrasonic waves by a Q-switched Nd:YAG laser of small power in polymers by the example of polyvinyl chloride. The possibility of creating acoustic-point-sources in visco-elastic materials is confirmed. Explanation of the mechanism of generation of ultrasonic waves is proposed. Directivity amplitude patterns of the acoustic sources are determined using ultrasonic broadband of resonance frequencies: 1 MHz, 2.25 MHz, 5 MHz, and a head for acoustic emision. The directivity frequency pattern for a head 2.25 MHz is also determined.